Journalism and the Tale of the Other: The Invisibility of Lusophones in Brazil and the Identity Erasure Between Us - Góes, José Cristian; Antunes, Elton (Brazilian journalism research, 2017)
The Community of Portuguese Language Countries (CPLP) has completed two decades of existence. Since Brazil is the largest Portuguese-speaking nation, our objective was to investigate how Folha de S.Paulo and O Globo have been reporting on this community over its 20-year history. Initial findings reveal a widespread invisibility of lusophones in Brazil. Scouring through the news reports over this short period, we found some hints that might have contributed to the invisibility of this community in Brazil. We then had to reflect on identities, globalization and community. At the center of this discussion, the fabulation over of the Other, who, in the CPLP, mostly come from black and African descent. Six of the nine Lusophone countries are from Africa. We suggest that the invisibility of lusophony in Brazil is erasing the identity between us, the people of this community. A Comunidade dos Países de Língua Portuguesa (CPLP) completou duas décadas. Como o Brasil é a maior nação lusófona, nosso objetivo foi investigar como a Folha de S.Paulo e O Globo noticiaram essa comunidade em seus 20 anos. A constatação inicial é da ampla invisibilização da lusofonia no Brasil. Ao escavar as poucas noticias desse longo período, percebemos indícios históricos e identitários na opção por tornar invisível essa comunidade no Brasil. Isso nos obrigou a refletir sobre identidades, globalização e comunidade. No centro dessa discussão, a fabulação sobre o Outro, que em relação a CPLP é majoritariamente negro e africano. Dos nove países lusófonos, seis são da África. Sugerimos que a invisibilização da lusofonia no Brasil passa pela tentativa de apagar os laços identitários entre Nós, povos dessa comunidade. La Comunidad de Países de Lengua Portuguesa (CPLP) ha completado dos décadas. Como Brasil es el mayor país de esta comunidad, nuestro objetivo era investigar cómo la Folha de São Paulo y O Globo informó duante este largo período. El hallazgo inicial es la invisibilidad amplia del lusofonia en Brasil. Mientras que la excavación de las pocas noticias, vemos evidencia histórica y de la identidad en la elección de invisibilizar esta comunidad en Brasil. Esto nos obliga a reflexionar sobre la identidad, la globalización y la comunidad. En el centro de esta discusión, la fábula sobre el Otro, que por CPLP es sobre todo negro y africano. De los nueve países de habla portuguesa, seis se encuentran en África. Sugerimos que la invisibilidad del habla portuguesa en Brasil implica el intento de borrar los lazos de identidad entre Nosotros, la gente de esta comunidad.